Advances in oil crops research-classical and new approaches to achieve sustainable productivity - Miladinović, Dragana (2019)
The world production of main oil crops is steadily increasing, mainly due to population growth and increased use of oil crops in bio-fuel production and in edible vegetable oils. From the perspective of sowing area in the world, oil crops are only preceded by cereals in importance. Edible or industrial oils are extracted from seeds, fruits or mesocarp, and nuts of both annual and perennial species. Oil can be obtained from about 40 different crops, but soybean, sunflower, olive tree, and rapeseed have a major importance in the total world trade. The purpose of the Research Topic “Advances in Oil Crops Research—Classical and New Approaches to Achieve Sustainable Productivity” is to provide the reader compiled information of the latest research results about different aspects of oil crops. This research topic incorporates 23 publications including 19 research papers, three review articles, and one perspective.